Leadership’s Soft Skills: A Key for Successful Educational Administrators (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Educational administrators operate in dynamic institutional environments where interpersonal effectiveness is as important as managerial and technical competence. This study explores the critical role of leadership soft skills in fostering successful educational administration. It identifies essential soft skills, examines their influence on institutional outcomes, and proposes a Leadership Soft Skill Model tailored for educational leaders. Findings from existing research highlight emotional intelligence, communication, collaboration, adaptability, and ethical decision-making as core competencies that enhance school climate, teacher motivation, and administrative efficiency. The study concludes with a conceptual model and suggests future research directions to expand empirical understanding of soft-skill–based educational leadership.